Electrochemotherapy vs radiotherapy in the treatment of primary cutaneous malignancies or cutaneous metastases from primary solid organ malignancies: a protocol for a systematic review and meta-analysis. Issue 1 (21st February 2022) - McMillan, Angus; McElroy, Luke; O'Toole, Lorcan; Matteucci, Paolo; Totty, Joshua P
Abstract: Electrochemotherapy has emerged as a valuable tool in the treatment of cutaneous malignancies that are unamenable to surgical resection. Despite growing recognition and recommendation in national guidelines, to date, no Level 1 evidence exists comparing its use to radiotherapy in the management of cutaneous malignancies. A systematic review and meta-analysis will be undertaken in line with the Cochrane Handbook and Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement and checklist. A comprehensive search strategy will be applied to MEDLINE, Embase, CINAHL, CENTRAL and ClinicalTrials.gov from the time period from inception to December 2021. Supplementary searches of the grey literature will also be undertaken. Studies in humans which compare treatment with electrochemotherapy to radiotherapy and report tumour response with at least a 4-week follow-up will be eligible. Studies will be included regardless of publication language or country of origin. Screening of studies and data extraction will be undertaken independently by two authors. Our primary outcome will be tumour volume response according to Response Evaluation Criteria in Solid Tumors. We will also extract any secondary outcomes reported, such as patient-reported outcome measures, pain, toxicity/adverse events and progression-free survival. Included studies will be assessed for risk of bias using recognized tools. Evidence quality will be appraised using the Grading of Recommendations, Assessment, Development and Evaluation approach. If studies are of acceptable clinical homogeneity and suitable data is extracted, a meta-analysis will be performed. If adequate data are present, various subgroup analyses will be performed. Publication bias will be assessed using a funnel plot and Egger's test. PROSPERO CRD42021285415